2023
DOI: 10.1002/ep.14196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment parameters and binder concentration on the densification of wood residue

Abstract: Pakistan is a farming and agricultural country facing energy issues from many years due to an increase in population and lack of technological development. Biomass is usually considered a waste. It is a major renewable energy source that is abundantly present in Pakistan. The wood residue is one of the potential biomasses to be used for energy purposes. Wood residue densification is considered a source of energy in this article. The effect of different pretreatments and binders (natural and synthetic) concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Additionally, new thermal processing technologies might make biomass pellet production more profitable [32][33][34]. Research efforts should also focus on identifying suitable raw materials for use as additives in pellet production, as not all biomass materials are appropriate for this purpose [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, new thermal processing technologies might make biomass pellet production more profitable [32][33][34]. Research efforts should also focus on identifying suitable raw materials for use as additives in pellet production, as not all biomass materials are appropriate for this purpose [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in structural results for NB and SB pellets might be due to the presence of organic and inorganic constituent's in sugar cane trash which causes SB to form compact and strong pellets while for NB pellets binder failed to form strong bonding with particles. As literature suggested that wood residue [40] and bagasse [16] pellets show better results for NB (LGBRB) instead of SB (LSBSB). In SB pellets a different type of bonding mechanism was identi ed due to the formation of lignin bridge and mechanical interlocking [41].…”
Section: Structural Analysismentioning
confidence: 99%